CodePlex: Software Complexity Measuring Tool based on ECB Measure - Dharmathilake K. A. D. K. D; Nuwanthika P. G. P. J.; Fernando N. K. B.; Bhanuka H. L. (International Journal of Engineering and Management Research, 2023)
The surge in popularity of object-oriented programming as a predominant paradigm in software development has spurred numerous studies to introduce metrics for assessing the complexity of object-oriented programs. These metrics typically fall into two primary categories: those focusing on object-oriented aspects and those centered on cognitive aspects, delineating their principal areas of concern when evaluating program complexity. Within the realm of cognitive aspects, the majority of metrics have historically been confined to the consideration of no more than three complexity variables. However, the ECB (Enhanced Cognitive Based) measure stands as a notable exception, capable of encompassing and addressing four or more intricate facets in the assessment of software program intricacy and difficulty. This research paper undertakes the exploration of the incorporation of these multidimensional metrics as refinements to the existing weighted composite complexity CB measure, originally introduced by Chhillar and Bhasin. In doing so, it endeavors to furnish a more comprehensive and holistic framework for the evaluation of program complexity, accommodating both object-oriented and cognitive dimensions. Furthermore, the study assumes the pivotal role of empirically validating the practical effectiveness of the ECB measure, seeking to bridge the chasm between theoretical metrics and their tangible applicability in real-world settings. Such an endeavor holds profound significance for software developers and researchers, proffering invaluable insights that can advance our understanding and management of intricate object-oriented programs.